Exploring Environmental Interactions Through Complex Networks: A Multilayer Analysis Of Ecological Relationships - Murtaja. Natiq Faris , Kheirolah Rahsepar.Fard (Migration Letters, 2024)
This abstract presents a comprehensive study on environmental interactions utilizing complex network theory. The research focuses on employing a multilayer analysis framework to unravel the intricate web of ecological relationships. By leveraging the principles of network science, this study aims to elucidate the interconnectedness and dynamics within ecosystems. The methodology involves constructing multilayer networks that encapsulate various ecological dimensions, including species interactions, food webs, habitat networks, and environmental factors. By integrating these layers, the research endeavours to reveal emergent properties and synergies existing across these interconnected systems. Through the application of advanced analytical tools, the study aims to identify key nodes, central motifs, and structural patterns within the multilayered ecological networks. Additionally, the research seeks to investigate the resilience of these networks to perturbations, providing insights into the stability and robustness of ecological communities in response to environmental changes.